2006
DOI: 10.1111/j.1469-8137.2006.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Do high‐nickel leaves shed by the nickel hyperaccumulator Alyssum murale inhibit seed germination of competing plants?

Abstract: Summary• Elemental allelopathy suggests that nickel (Ni)-rich leaves shed by hyperaccumulators inhibit the germination and growth of nearby plant species.• Here, the germination of eight herbaceous species following addition of Alyssum murale biomass or Ni(NO 3 ) 2 , with the same Ni level added to soil, was assessed. The distribution of Ni in soil was tested by determining Ni phytoavailability and speciation over time.• Phytoavailable Ni in soil amended with biomass declined rapidly over time due to Ni bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…Work on Allysum murale (Zhang et al 2005) demonstrated the mineralization of Ni from plant litter and analyzed the effect on Ni bioavailability in soils. The authors questioned whether sorption by soil would buffer any effects and later confirmed that the increase in Ni did not inhibit germination (Zhang et al 2007). Again the separation of the effect of elemental allelopathy from pre-existing elevated Ni levels would be necessary since the plants that released the most Ni into the soil were the ones that were grown on Ni-rich soils.…”
Section: Heavy Metalsmentioning
confidence: 97%
See 1 more Smart Citation
“…Work on Allysum murale (Zhang et al 2005) demonstrated the mineralization of Ni from plant litter and analyzed the effect on Ni bioavailability in soils. The authors questioned whether sorption by soil would buffer any effects and later confirmed that the increase in Ni did not inhibit germination (Zhang et al 2007). Again the separation of the effect of elemental allelopathy from pre-existing elevated Ni levels would be necessary since the plants that released the most Ni into the soil were the ones that were grown on Ni-rich soils.…”
Section: Heavy Metalsmentioning
confidence: 97%
“…Isolate and characterize toxin Vivrette and Muller (1977), Morris et al (2006) Determine toxin levels found naturally in accumulator species, rates of deposition, and accumulation in soils Sharma and Tongway (1973), Vivrette and Muller (1977), Boyd et al (1999), Boyd and Jaffre (2001), Zhang et al (2005Zhang et al ( , 2007 Select proper bioassay based on Vivrette and Muller (1977), Lesica and Deluca (2004), Morris et al (2006) growth form species phenology Determine uptake and symptoms of the toxin in affected species Vivrette and Muller (1977), Morris et al (2006) Source: Adapted from Fuerst and Putnam (1983) Plant Ecol (2009) 202:1-11 5 which concentrate their roots at the soil surface, may be better candidates. For species which are thought to phytoenrich elements through acidification or other modifications of the rhizosphere, root architecture may not be as important.…”
Section: Criteria For Determining Elemental Allelopathymentioning
confidence: 99%
“…The flora of Sabah has an estimated 8000 vascular plant species (Wong 1992) with over 5000 plant species in the \1200 km 2 Kinabalu Park (Beaman 2005). Prior to this study, the following Ni hyperaccumulators were known to occur in Sabah: Rinorea bengalensis and R. javanica (Violaceae) Brooks et al 1977), Phyllanthus balgooyi (Phyllanthaceae) (Baker et al 1992;Hoffmann et al 2003), Dichapetalum gelonioides (Dichapetalaceae) (Baker et al 1992), Psychotria cf.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have shown that metal-accumulating plants are better able to defend against fungal and insect attacks as well as herbivores (Boyd and Martens, 1998;Boyd, 2004). Another hypothesis for the benefit of metal hyperaccumulation is "elemental allelopathy", which is the deterrence of colonization of other plants in the zone beneath hyperaccumulator plants (Zhang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%